ATP-binding cassette transporter A1 gene polymorphisms and serum lipid levels in young Greek nurses - Degiannis Dimitrios; Kalogiani Antonia; Vasilopoulos Georgios; Karakosta Agathi; Marvaki Apostolia; Kolovou Genovefa; Kolovou Vana; Marvaki Christina; Demopoulos Constantinos A (Lipids in Health and Disease, 2011)
Abstract Objective The ATP-binding cassette transporter A1 (ABCA1) is essential protein involved in lipid metabolism. The present study was undertaken to detect the possible association of polymorphisms in the ABCA1 gene [rs2230806 (R219K) and rs2230808 (R1587K)] and lipid profile in Greek young nurses. Methods The study population consisted of 308 unrelated nurses who were genotyped and the ABCA1 polymorphisms were detected. Additionally, lipid profile [total cholesterol (TC), triglycerides (TGs), high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C) and apolipoprotein (apo) A] was evaluated. Results There was no difference in the genotypic and allelic frequencies of the R219K polymorphism according to lipid profile. The R1587K genotypes differed significantly according to TC, LDL-C and TGs concentration (p = 0.023, p = 0.014 and p = 0.047, respectively). Particularly, significant difference in TC, LDL-C and TGs concentration was detected between RK and RR genotypes (p = 0.006, p = 0.004, p = 0.014, respectively). Women with RK genotype compared to RR genotype had higher concentration of TGs (134.25 mg/dl vs 108.89 mg/dl, p = 0.014, respectively), total cholesterol (207.41 mg/dl vs 187.69 mg/dl, p = 0.006, respectively), and LDL-C (110.6 mg/dl vs 96.9 mg/dl, p = 0.004, respectively). Conclusions These findings suggest that the R1587K polymorphism of ABCA1 gene was associated with lipid profile of Greek nurses. Women with RK genotype had higher TGs, total and LDL-C concentration compared to RR genotype. These observations may be significant in assessing the risk of CAD since a 1% change in LDL-C is associated with a 1% change of cardiovascular events. Also, TGs concentration were documented to play a significant role in women. However, this needs to be confirmed by larger studies.